Source apportionment of VOCs and their impact on air quality and health in the megacity of Seoul. (April 2019) - Song, Sang-Keun; Shon, Zang-Ho; Kang, Yoon-Hee; Kim, Ki-Hyun; Han, Seung-Beom; Kang, Minsung; Bang, Jin-Hee; Oh, Inbo
Abstract: The source apportionment of volatile organic compounds (VOCs) was examined using receptor models (positive matrix factorization and chemical mass balance) and a chemical transport model (CTM). The receptor model-based analysis was performed using the datasets collected from four different sites from the megacity of Seoul during the years 2013–2015. The contributions of VOC emission sources to ozone (O3 ) and PM2.5 concentrations and the subsequent health effects in the study area were also assessed during a photochemically active period (June 2015) using a three-dimensional CTM, Community Multi-scale Air Quality (CMAQ), and the Environmental Benefits Mapping and Analysis Program (BenMAP). The solvent use and the on-road mobile emission sources were found to exert dominant controls on the VOC levels observed in the target city. VOCs transported from regions outside of Seoul accounted for a significant proportion (up to approximately 35%) of ambient VOC levels during the study period. The solvent use accounted for 3.4% of the ambient O3 concentrations during the day (daily mean of 2.6%) and made insignificant contributions to PM2.5 (<1%) during the simulation period. Biogenic VOC made insignificant contributions to O3 (<1%) and a small contribution to PM2.5 during the day (5.6% with a daily mean of 2.4%). The number of premature deaths attributed indirectly (O3 and PM2.5 formations via the oxidation of VOCs) to solvent use is expected to be significant. Graphical abstract: Image 1 Highlights: The solvent use and the on-road mobile emission sources exert dominant controls on the VOC levels. VOCs transported from regions outside of Seoul accounted for a significant proportion of ambient VOC levels. Biogenic VOC made insignificant contributions to O3 and PM2.5 The number of premature deaths attributed indirectly to solvent use is expected to be significant.